SCIENCE PUBLIC HALL SEBAGAI WADAH PENYAMPAIAN SAINS TERAPAN DAN TEKNOLOGI TEPAT GUNA KEPADA MASYARAKAT DENGAN PENDEKATAN GREEN ARCHITECTURE - Rizky Antofagasta; Hardiyati Hardiyati; Amin Sumadyo (Universitas Sebelas Maret Surakarta, 2014)
Abstract: This facility has a purpose to improve life quality of the society by applied science and efficient technology. For that, Yogyakarta is the fine city because it has a vision to become the central of education in Indonesia supported by society of knowledge and technology. To achieve that purpose, Science Public Hall provides several main functions and activities that which are; workshop, convention, exhibition, and library. Besides green architecture is also part of applied science and efficient technology in the sector of architecture, so that would be appropriate to apply green building in purpose to spreading environmentally architecture to the people. Keyword: The Society, Applied Science and Efficiemt Technology, Green Architecture